Seismic response analysis of nuclear island building: A case study - Jaya, V.; Dodagoudar, G. R.; Boominathan, A. (Journal of Structural Engineering, 2024)
The objective of the paper is study the effects of Soil-Foundation-Structure Interaction (SFSI) on seismic response of a deeply embedded Nuclear Island Building (NIB) using the fi nite element method. The interaction analysis of the NIB is carried out using flexible volume substructure method (FVSM). The SFSI model of the embedded NIB is subjected to a site-specifi c design ground motion. The computations required to study the seismic response of the NIB are accomplished using the program SASSI 2000. The present study is restricted to the evaluation of floor acceleration response spectrum and acceleration time-history at the selected locations along the heights of the eight buildings housed in the NIB. The floor response spectra (FRS) are useful for the earthquake resistant design of secondary systems located at different floor levels of the NIB. It is noted that the design of nuclear power plant structures should take into account the effect of embedment provided by the engineered backfill.